EVALUATION OF THE FOREIGN POLICY DEVELOPMENTS OF THE DEMOCRATIC PARTY PERIOD IN TURKISH POLITICAL LIFE - Acar, Hasan (Bursa Teknik Üniversitesi, 2020)
This article discusses the peaceful methods followed by the Democrat Party, which is important in Turkish political life between 1950-1960 and its effective politics in foreign policy. First, the Republic of Turkey will be evaluated the relations within the foreign policy after the Second World War. Secondly, developments in foreign policy during the Democratic Party period will be evaluated in the context of bilateral relations. In this context, Turkish-American relations, Turkish-Soviet Union relations, Turkish-British relations, Cyprus issue, Turkish-Greek relations will be discussed. Third and finally, alliances and associations established in foreign policy were evaluated during the Democratic Party period. For this purpose, during the period of the Democratic Party, established partnerships with the Balkans, the Baghdad Pact, the Bandung Conference and the European Union-Turkey relations will be discussed. Thus, the developments in Turkish foreign policy between 1950-1960 will be evaluated.

Bu makalede, Türk siyasi hayatında 1950-1960 yılları arasında önemli olan Demokrat Parti'nin izlediği barışçıl yöntemler ve dış politikadaki etkili siyaseti tartışılmaktadır. İlk olarak, Türkiye Cumhuriyeti’nin, İkinci Dünya Savaşı sonrasında dış politikadaki ilişkileri değerlendirecektir. İkinci olarak, Demokrat Parti döneminde dış politikadaki gelişmeler ikili ilişkiler bağlamında değerlendirilecektir. Bu bağlamda Türk-Amerikan ilişkileri, Türk-Sovyetler Birliği ilişkileri, Türk-İngiliz ilişkileri, Kıbrıs sorunu, Türk-Yunan ilişkileri tartışılacaktır. Üçüncü ve son olarak, Demokrat Parti döneminde dış politikada kurulan ittifaklar ve birliktelikler değerlendirilmiştir. Bu amaçla Demokrat Parti döneminde Balkanlar, Bağdat Paktı, Bandung Konferansı ve Avrupa Birliği-Türkiye ilişkileri ile kurulan ortaklıklar tartışılacaktır. Böylece Türk dış politikasındaki 1950-1960 yılları arasındaki gelişmeler değerlendirilecektir.
EVALUATION OF THE FOREIGN POLICY DEVELOPMENTS OF THE DEMOCRATIC PARTY PERIOD IN TURKISH POLITICAL LIFE
Keywords: Political Science; Siyaset Bilimi